Primary follicular lymphoma of the breast – Case report - Bruno P Fogaça Duarte; Julia Saccaro Duzzi; José Gabriel K Francisco Petillo; Geovanna Vieira Araújo; Angelo Sementilli (Oncología)
Introduction: Primary follicular lymphoma of the breast is a rare entity with unique clinical and pathological features. This report highlights the diagnostic challenges and management of this condition. Case presentation: A 63-year-old patient presented with an irregular nodule in the left breast, which was classified as BIRADS IV/C on core needle biopsy. Suspecting an intramammary tumor, she was referred for surgical excision. Histopathological and immunohistochemical studies confirmed a grade 1/2 follicular lymphoma. Conclusion: This case highlights the importance of integrating imaging, histology and immunohistochemistry for accurate diagnosis of primary mammary follicular lymphoma. Early multidisciplinary management is crucial for a favorable outcome.